A report on the practice in industry training in fish culture y Leo R. Bargas. - Bargas, Leo R. (College of Fisheries, University of the Philippines, 1958)
Two years of theoretical instruction from the Philippine Institute of Fisheries Technology is not enough to equip a student to face the practical side of his chosen vocation although some practical training is given in the laboratory subjects. One who has met all the requirements in his or her academic subjects from Philippine Institute of Fisheries Technology needs to undergo a six-month practical training with a certain company or an individual engage in this line of endeavour, to augment the theoretical knowledge from the classrooms. During this period of apprenticeship the students is not expected to instruct the men working with the firm, but he is bound to do whatever undertakings in some implementations could be introduced by an apprentice. This six months of apprenticeship is a pre-requisite to graduation. It is during this period that the student may develop their ability regarding public relations. In one way or another an observant apprentice may be able to find out the socio-economic status of the men with whom he came in contact directly during his practical training. Thus, he may have an idea regarding the problems of these people, that he may later recommend some solution for these problems.